2018
DOI: 10.1177/0363546517744535
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Clinical Results, Second-Look Arthroscopic Findings, and MRI Findings Between the Transportal and Outside-In Techniques for Double-Bundle Anatomic Anterior Cruciate Ligament Reconstruction: A Prospective, Randomized Controlled Trial With a Minimum 2-Year Follow-up

Abstract: With the exception of the functional test of IKDC objective score, we found that clinical results, second-look arthroscopic findings, and MRI findings did not differ significantly between the OI and TP techniques for anatomic ACL reconstruction, although femoral tunnel geometries differed significantly between the 2 techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 64 publications
0
31
0
Order By: Relevance
“…Two studies reported rehabilitation protocols. 11,19 One study reported partial weightbearing at 4 weeks with crutches and an increase in knee flexion range of motion to 120º at 4 weeks. 11 At postoperative 6 weeks, patients were allowed full weightbearing with a brace.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Two studies reported rehabilitation protocols. 11,19 One study reported partial weightbearing at 4 weeks with crutches and an increase in knee flexion range of motion to 120º at 4 weeks. 11 At postoperative 6 weeks, patients were allowed full weightbearing with a brace.…”
Section: Resultsmentioning
confidence: 99%
“…11,19 One study reported partial weightbearing at 4 weeks with crutches and an increase in knee flexion range of motion to 120º at 4 weeks. 11 At postoperative 6 weeks, patients were allowed full weightbearing with a brace. 11 The other study reported use of an ACL limited-motion brace applied 4 to 5 days after surgery, and joint motion exercise was carried out at 15° increments per week.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 2 However, residual instability, as indicated by degree of pivot shift, is still evident in some patients after ACLR, with a reported prevalence of 8% to 25%. 6 , 13 Several studies on knee instability have indicated that high-grade pivot shift and knee hyperextension preoperatively are risk factors for postoperative residual instability. 31 With respect to rotation at 30° and 90° of flexion (ie, rotational laxity), a considerable effect of initial knee laxity on postoperative outcomes has been reported.…”
mentioning
confidence: 99%